Combined NOx and noise pollution from road traffic in Trabzon, Turkey - KESKİN, SIDDIK SİNAN (ELSEVIER, 2019)
Environmental impacts of motor vehicles in the form of air and noise pollution have attracted more interest in recent years due to their relation with some health problems such as asthma, bronchitis, cardiovascular disease, myocardial infarction, and hypertension. Recently, it has been suggested that not only their individual effects but also their combined effects should be considered in public health studies. In this study, NOx and noise pollution levels were determined in Trabzon, a city in the Eastern Black Sea region of Turkey. For this purpose, a traffic emission inventory was prepared to be used in an air pollution modeling software to determine the concentrations of NOx, one of the primary pollutants from road traffic emissions, within the study area. Also, vehicle counts and types were determined to be used in noise pollution software to evaluate the noise pollution levels in the study area. Model results were compared to measurement data by using different statistical tools. Separate and combined exposures of the population to traffic-related NOx and noise emissions were examined together with meteorological and topographic effects on them. The relationship between NOx and noise pollution indicated that, they are highly correlated in two districts (Valilik and Meydan) out of the four examined in Trabzon city center, suggesting traffic is the dominant source for both. Results indicated that percentages of the population exposed to traffic-related NOx and noise levels above the regulatory limits were 10% and 21%, respectively. It was determined that 6% of the population, 29 school and 19 hospital buildings were exposed to both noise and NOx levels above the regulatory limits in the city center of Trabzon. These percentages should be considered as conservative since additional NOx and noise sources other than traffic might increase the exposure levels of the population. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Road traffic; NOx pollution; Noise pollution; Modeling; Correlation; Exposure; PARTICULATE MATTER CONCENTRATIONS; AMBIENT AIR-POLLUTION; LONG-TERM EXPOSURE; TRANSPORTATION NOISE; RAILWAY NOISE; IMPACT; ASSOCIATIONS; DISEASE; MODEL; HYPERTENSION